Unreliable Extended-Spectrum β-Lactamase Detection in the Presence of Plasmid-Mediated AmpC in Escherichia coli Clinical Isolates - Robberts, F. J. L. (American Society for Microbiology (ASM), 2009)
The emergence of extended-spectrum β-lactamase (ESBL) and plasmid-mediated AmpC (pAmpC) enzymes in Escherichia coli raises concern regarding accurate laboratory detection and interpretation of susceptibility testing results. Twenty-six cefpodoxime ESBL screen-positive, cefoxitin-resistant E. coli clinical isolates were subjected to clavulanate ESBL confirmatory testing employing disk augmentation, Etest, and the BD Phoenix NMC/ID-132 panel. Phenotypic pAmpC production was assessed by boronic acid disk augmentation. ESBL and pAmpC genes were detected by gene amplification and sequencing. ESBL genes (SHV and/or CTX-M-type genes) were detected in only 7/26 ESBL screen-positive isolates. Of 23 aminophenylboronic acid screen-positive isolates, pAmpC genes were detected in 20 (CMY-2 or FOX-5 genes). High incidences of false-positive ESBL confirmatory results were observed for both clavulanate disk augmentation (9/19) and BD Phoenix (5/19). All were associated with the presence of pAmpC genes with or without TEM-1. Etest performed poorly, as the majority of interpretations were nondeterminable. In addition, false-negative ESBL confirmatory results were observed in isolates possessing concomitant ESBL and pAmpC genes for Etest (four of five), BD Phoenix (three of five), and disk augmentation (one of five). The results indicate poor performance of currently employed ESBL confirmatory methods in the setting of concomitant pAmpC. Some isolates with pAmpC and ESBL genes fell within the susceptible category to extended-spectrum cephalosporins, raising concern over currently employed breakpoints.